2020
DOI: 10.1021/acsaem.0c01603
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Tailored Water Wettability on Performance of CO2 Capture

Abstract: The growing emission of CO 2 is a severe cause of concern due to its adverse impact on the environment and climate change worldwide. In the past, various approaches, including synthesis of porous materials and amino modifications, were adopted for efficient and direct separation of CO 2 from flue gas. Recently, hydrophobicity has been introduced to protect some of the highly potent porous materials and membranes from high humidity and aqueous exposures. While these approaches remained successful in removing CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Such materials would reduce water uptake/working capacity, while improving the stability of amine sites toward leaching and surface mobility. Several adsorbents, consisting of either a hydrophobic support , or hydrophobic organic moieties , with improved behavior in the presence of moisture, were reported in the literature. Guo et al used an amine-tethered polymer synthesized by copolymerization of glycidyl methacrylate, tert -butyl methacrylate, and trimethylolpropane triacrylate into microporous hydrophobic beads, followed by covalent immobilization of TEPA via epoxy groups.…”
Section: Amine-functionalized Adsorbentsmentioning
confidence: 99%
“…Such materials would reduce water uptake/working capacity, while improving the stability of amine sites toward leaching and surface mobility. Several adsorbents, consisting of either a hydrophobic support , or hydrophobic organic moieties , with improved behavior in the presence of moisture, were reported in the literature. Guo et al used an amine-tethered polymer synthesized by copolymerization of glycidyl methacrylate, tert -butyl methacrylate, and trimethylolpropane triacrylate into microporous hydrophobic beads, followed by covalent immobilization of TEPA via epoxy groups.…”
Section: Amine-functionalized Adsorbentsmentioning
confidence: 99%
“…Thereafter, Rather et al introduced amine amplified superhydrophobicity on cotton, where the residual chemical reactivity of CRPNC derived coating on cotton was covalently used to integrate BPEI, prior to modification with octadecylaminefollowing Michael addition reaction at ambient conditions. 68 Thereafter, the amine amplification aided in carbon dioxide capture through the formation of carbamic acids while the remaining acrylates were postmodified with increasing hydrophobic amine small molecules to evaluate the impact of water wettability on the carbon dioxide capture. It was concluded that "amine amplified" superhydrophobicity exhibited superior carbon dioxide capture in comparison to just a superhydrophobic substrate at practically harsh and diverse settings.…”
Section: Design Of "Reactive'' Interfaces Formentioning
confidence: 99%
“…Such characteristics are of utmost importance for realistic and diverse applications of the bioinspired coating. In this regard, the environment-friendly Michael addition reaction between amine and acrylate requiring mild operational conditions would provide a prospective platform to tailor the bioinspired water wettability and other relevant physical properties (Figure )including transparency, mechanical property, porosity, etc.following simple and scalable fabrication processes. In the past, the catalyst-free Michael addition reaction was successfully extended to produce amplified “reactive” surfaces. , Ford et al studied the ability of growing different nanostructures on selected substrates following the catalyst-free aza-Michael addition reaction between branched polyethylenimine (BPEI) and dipentaerythritol penta-acrylate (5-Acl) that resulted in hyperbranched poly­(ester amines) cross-linked thin films with surface amplified functional groups . In 2012, Bechler et al capitalized on this concept of a nanostructured, “reactive” polymeric film of BPEI/5Acl to construct a relatively thick (∼750 nm) multilayer coating following the layer-by-layer deposition approach .…”
Section: Design Of “Reactive’’ Interfaces For Superhydrophobicity: Su...mentioning
confidence: 99%
See 2 more Smart Citations